Tanggung Jawab Direksi Atas Keputusan Bisnis yang Merugikan Pihak Ketiga dalam Hukum Perseroan Terbatas Indonesia - Damanik, Saka Baja Pratama (Universitas Batanghari Jambi, 2024)
This research aims: to find out the responsibility of the Board of Directors for business decisions that harm third parties in Indonesian limited liability company law; The problems in this research are: what is the responsibility of the Board of Directors for business decisions that are detrimental to third parties in Indonesian limited liability company law; The research method used is the normative juridical research method and the approaches used are the Conceptual Approach and Legislative Approach.. Analysis of the legal materials used in this research was carried out using descriptive analytical research methods, the data analysis used was a qualitative approach to primary and secondary data. The results of the research show that under Indonesian Limited Liability Company law, third parties can only hold the Directors' personal responsibility to the extent of the Directors' actions in making incorrect financial reports and the Directors' actions which caused the Limited Liability Company to go bankrupt. Apart from wrongdoing in preparing financial reports and causing the Limited Liability Company to go bankrupt, the Directors are not personally responsible for losses to third parties caused by legal violations committed by the Limited Liability Company, even if the violation originates from the Directors' business decisions.